Charge-Based Inhibitors of Amylin Fibrillization and Toxicity - Sharadrao M. Patil; Andrei T. Alexandrescu (Journal of Diabetes Research)
To test the hypothesis that electrostatic repulsion is an important force opposing amyloid fibril assembly, we designed peptides that substitute strings of positively or negatively charged residues into the sequence of the amyloidogenic hormone amylin, which contributes to type 2 diabetes pathology. Arg-1 and Arg-2 substitute four positively charged arginines for segments that in structural models of amylin fibrils form the end of strand β1 and the beginning of strand β2, respectively. Mem-T substitutes negatively charged aspartates for the peptide segment with the largest avidity for membranes. All three charge-loaded peptides fibrillize poorly on their own and inhibit fibril elongation of WT-amylin at physiological ionic strength. The inhibition of WT-amylin fibril elongation rates is salt-dependent indicating that the analogs act through electrostatic interactions. Arg-1 protects against WT-amylin cytotoxicity towards a MIN6 mouse model of pancreatic β-cells, and Arg-2 protects at higher concentrations, whereas Mem-T has no effect. The most effective variant, Arg-1, inhibits WT-amylin fibril elongation rates with an IC50 of ~1 µM and cytotoxicity with an IC50 of ~50 µM, comparable to other types of fibrillization inhibitors reported in the literature. Taken together, these results suggest that electrostatic interactions can be exploited to develop new types of inhibitors of amyloid fibrillization and toxicity.